Comunicação pública : a TV legislativa local-regional como canal de informação de interesse público - Souza, Fernando Moreira de (2021)
The purpose of this research is to analyze the potential of legislative TVs as vehicles of information of public interest. The research is based on the understanding that state and public media develop public communication functions not covered by private media, considering the limitations imposed by the commercial network model and the limited space for local and regional content. Thus, the research has the general objective of understanding the extent to which state and municipal legislative TVs can contribute to broadening the media visibility of issues and themes relevant to local and regional contexts. To this end, we adopted the TV Assembleia Legislativa de Sergipe (TV Alese) and TV Câmara de Aracaju (TV CMA) as the object of study, as two local vehicles that make up the Legislative Digital TV Network (Rede Legislativa de TV Digital, in Portuguese), maintained by TV Câmara dos Deputados and TV Senado. The perspective that guides the proposed approach is that the legislative media carry out a work of producing informative content that amplifies the transparency function of the legislative houses, constituting itself as a space of media visibility for issues and themes of local interest. Thus, the research describes and analyzes the functioning of legislative TVs in view of the specificities of this type of broadcaster and its network organization logic, which differs from both commercial media and public and state media centralized in the Executive Power. In this scenario, the creation of the Legislative Digital TV Network represents the construction of a new network model that, if used in favor of the public interest, can favor experiences with public communication focused on local and regional issues. In the methodological aspect, the present research consists in a study of two cases and uses a combination of different research techniques to enable the explanation of the object, including: bibliographic review on the themes of public communication, public TV and legislative TV; documentary analysis of normative instruments on these subjects; field research, involving the application of questionnaires and conducting in-depth interviews with professionals from the two broadcasters. The analysis aims to understand the operation of local legislative broadcasters and what functions they perform in practice, considering the testimonies of professionals working on TV Alese and TV CMA, the analysis of programming schedules and the comparison with other models of national and international legislative TVs. The results of the research show that TV Alese covers legislative activities and develops local and regional news coverage, while TV CMA dedicates itself only to the actions of the Legislative House